2018
DOI: 10.1038/s41420-018-0028-7
|View full text |Cite
|
Sign up to set email alerts
|

GRK2 moderates the acute mitochondrial damage to ionizing radiation exposure by promoting mitochondrial fission/fusion

Abstract: The modern understanding of the G protein-coupled receptor kinase 2 has grown towards the definition of a stress protein, for its ability to rapidly compartmentalize within the cell in response to acute stimulation. Also, mitochondria can be regulated by GRK2 localization. We show that Ionizing Radiation (IR) exposure acutely damages mitochondria regarding mass, morphology, and respiration, with recovery in a framework of hours. This phenomenon is actively regulated by GRK2, whose overexpression results to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…Studies have shown data that GRK may act both a protector against and a promotor for death following ischemic injury (45,53). Removal of cardiac-specific GRK2 has been linked to embryonic cardiovascular development, adult cardiac dilatation, early atherosclerosis and inhibited angiogenesis in mice (42,(54)(55)(56)(57). Franco et al evaluated cell cultures with knockdown or overexpressed GRK2 3-8 h after exposure of a single dose of 4 Gy.…”
Section: Mitochondria and Oxidative Stressmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have shown data that GRK may act both a protector against and a promotor for death following ischemic injury (45,53). Removal of cardiac-specific GRK2 has been linked to embryonic cardiovascular development, adult cardiac dilatation, early atherosclerosis and inhibited angiogenesis in mice (42,(54)(55)(56)(57). Franco et al evaluated cell cultures with knockdown or overexpressed GRK2 3-8 h after exposure of a single dose of 4 Gy.…”
Section: Mitochondria and Oxidative Stressmentioning
confidence: 99%
“…Franco et al evaluated cell cultures with knockdown or overexpressed GRK2 3-8 h after exposure of a single dose of 4 Gy. Knockdown of GRK caused morphologic mitochondrial changes, reduced membrane potential and reduced mitochondrial function (42). The overexpression of GRK2 protected mitochondria from radiation damage (42).…”
Section: Mitochondria and Oxidative Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…7 In particular, alterations of cardiac metabolism are an early marker of HF that anticipates the systolic dysfunction and ventricle remodelling. 7 Furthermore, GRK2 localizes at mitochondria 8 where it seems, in the long run, to promote a pro-death signal pathway. 9 Although previous literature shows the possibility to restore cardiac contractility by targeting GRK2 with different strategies, so far, no information is available as to the effects of GRK2 inhibition on cardiac metabolism and mitochondrial function in the failing heart.…”
Section: Introductionmentioning
confidence: 99%